2021
DOI: 10.2196/27205
|View full text |Cite
|
Sign up to set email alerts
|

Usability Testing of a Digital Assessment Routing Tool: Protocol for an Iterative Convergent Mixed Methods Study

Abstract: Background Musculoskeletal conditions account for 16% of global disability, resulting in a negative effect on millions of patients and an increasing burden on health care utilization. Digital technologies that improve health care outcomes and efficiency are considered a priority; however, innovations are often inadequately developed and poorly adopted. Further, they are rarely tested with sufficient rigor in clinical trials—the gold standard for clinical proof of efficacy. We have developed a new m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…The G-MoMo applications are efficient since users take less time to complete tasks accurately. This reconfirmed the results of earlier studies by (A'bas et al, 2021;Hussain and Omar, 2020;Lowe et al, 2021;Zakaria et al, 2020), where they found the applications efficient for the users. The users also agreed that they would remember navigating between G-MoMo applications pages the next time they use it.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The G-MoMo applications are efficient since users take less time to complete tasks accurately. This reconfirmed the results of earlier studies by (A'bas et al, 2021;Hussain and Omar, 2020;Lowe et al, 2021;Zakaria et al, 2020), where they found the applications efficient for the users. The users also agreed that they would remember navigating between G-MoMo applications pages the next time they use it.…”
Section: Discussionsupporting
confidence: 88%
“…The users achieved satisfaction with the features, functionalities, design, information and display quality of the G-MoMo applications. This finding was also reported in earlier studies by (A'bas et al, 2021;Al-Gayar et al, 2021;Lowe et al, 2021;Putri et al, 2021), where they observed that the users were satisfied with the applications' functionalities and design. The participants mentioned that the G-MoMo applications were easy to use, which helped them achieve satisfaction.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Real-world usability testing has been completed using an iterative convergent mixed methods design incorporating patient and public involvement [42], the results of which will be reported later in 2021. This study optimized usability in the final DART iteration that will be used in this pilot study and subsequent main trial.…”
Section: Previous Workmentioning
confidence: 99%
“…An iterative, convergent mixed methods design was used to assess the usability of DART, using cyclical evaluation and improvement plus mixed methods to provide richness while quantifying use, maximizing usability, and therefore supporting system adoption [ 34 ]. The testing protocol for this study has been described in detail in a previous publication [ 35 ].…”
Section: Introductionmentioning
confidence: 99%